Superselective Embolization with Microcoil and Gelfoam for High-Flow Priapism Secondary to Bilateral Cavernous Fistulae: A Case Study - Sarah Prattley; Timothy Bryant; Rowland Rees (Case Reports in Urology)
Background. High-flow priapism is rare, and bilateral arteriocavernous fistulae formation following trauma is rarer still. Management of high-flow priapism is conservative either through observation, use of ice packs, mechanical decompression, or intracavernosal injection of α-adrenergic agonists, giving temporary results in selected cases. Alternatively, superselective arteriography with embolization is widely accepted. However, intervention needs to be mindful of the potential impact on long-term potency. We report the first case of bilateral arteriocavernous fistulae managed with both Gelfoam and microcoil embolization. Case Study. We present the case of a 35-year-old gentleman who attended the emergency department nine days following a fall from a moped, where he sustained bruising to his perineum, with persistent nonpainful erection. CT angiogram demonstrated bilateral arteriovenous fistulas. Management with superselective catheterisation and embolization with Gelfoam and microcoil was successful with resolution of symptoms. Long-term follow-up has shown return to normal erectile function twelve months following the injury. Outcomes. Concern regarding the effect to long-term erectile function has previously led to delayed bilateral embolization. Selection of embolization material can be tailored to the anatomical features of the fistula to help preserve function.